Draft Genome Sequence of Bacillus thuringiensis INTA 103-23 Reveals Its Insecticidal Properties: Insights from the Genomic Sequence - Palma, Leopoldo; Ortiz, Leila Melina; Niz, José María; Berretta, Marcelo Facundo; Sauka, Diego Hernan (MDPI, 2024)
The genome of Bacillus thuringiensis strain INTA 103-23 was sequenced, revealing a high-quality draft assembly comprising 243 contigs with a total size of 6.30 Mb and a completeness of 99%. Phylogenetic analysis classified INTA 103-23 within the Bacillus cereus sensu stricto cluster. Genome annotation identified 6993 genes, including 2476 hypothetical proteins. Screening for pesticidal proteins unveiled 10 coding sequences with significant similarity to known pesticidal proteins, showcasing a potential efficacy against various insect orders. AntiSMASH analysis predicted 13 biosynthetic gene clusters (BGCs), including clusters with 100% similarity to petrobactin and anabaenopeptin NZ857/nostamide A. Notably, fengycin exhibited a 40% similarity within the identified clusters. Further exploration involved a comparative genomic analysis with ten phylogenetically closest genomes. The ANI values, calculated using fastANI, confirmed the closest relationships with strains classified under Bacillus cereus sensu stricto. This comprehensive genomic analysis of B. thuringiensis INTA 103-23 provides valuable insights into its genetic makeup, potential pesticidal activity, and biosynthetic capabilities. The identified BGCs and pesticidal proteins contribute to our understanding of the strain’s biocontrol potential against diverse agricultural pests.